Teaching across semiotic modes with multilingual learners: translanguaging in an Australian classroom. (4th March 2019) - Ollerhead, Sue
Abstract: Despite the growing numbers of migrant students enrolling in Australian secondary schools, and an official acknowledgment of their complex support and learning needs, there has been little policy focus on the pedagogical changes that need to be made by teachers to accommodate these needs. There is also little understanding of the depth and diversity of linguistic resources and cultural funds of knowledge that migrant students bring to Australian classrooms, and the ways in which these might enrich classroom learning experiences for all students. This paper draws upon data from a qualitative, ethnographically oriented case study research project in which teachers and researchers collaborated to enact bottom up language policy that involved the use of translanguaging (Garcia, 2009) to enhance communication and classroom learning amongst multilingual students from migrant backgrounds. The aim was to draw upon students' observable languaging practices from their full repertoire of languages, and to tap into their existing cultural and linguistic funds of knowledge to support their academic language development and foster their linguistic and personal identities in the classroom.